Determination of Selected Heavy Metal Contents in Fresh and Smoked Corbicula Fluminea (Muller, 1774) Collected from Hawkers in the District of Tumpat, Kelantan, Malaysia Running Head: Heavy Metal Content in C.fluminea Tumpat’s Hawkers - Aweng E.R., Nurul Inani R., Arham Muchtar A.B., M.A. Salam, Sharifah Aisyah S.O., Liyana A.A., M. Mazlan (International Journal of Advanced Science and Technology, 2020)
Apart being contaminated at the habitat, Corbicula fluminea (C. fluminea) was also believed to be contaminated at the selling point caused by the dust from the roadside as well as old newspaper wrapping used by hawkers. This situation can cause discomfort among smoked C. fluminea also known as “etak salai” (as per Kelantanese dialect) enthusiasts because it is commonly associated with poor hygiene and health problem. Therefore, this study aims to determine and evaluate the concentration of selected heavy metal (Cr, Zn, Mn and Cu) contents in fresh and smoked C. fluminea collected from hawkers in the district of Tumpat, Kelantan, Malaysia. Wet digestion method was used to extract the samples and the samples were tested using air acetylene flame atomic absorption spectrometry (AAS). Result shows that, fresh C. fluminea has higher concentrations as compared to smoked C. fluminea which are sold at the stall of all measured parameters except for Cr (fresh: 0.14 mg/kg and smoked: 0.22 mg/kg). However, Zn is the highest concentrations heavy metal in C. fluminae (fresh: 74.39 mg/kg and smoked: 35.41 mg/kg) compared to other parameters. Cr and Zn concentrations in fresh and smoked C. fluminea are below the stipulated standard of Malaysia Food Regulation, 1985 (0.50 mg/kg for Cr; 100 mg/kg for Zn) and Food Standard Australia and New Zealand standards, 1991 (100 mg/kg). However, Mn concentrations in C. fluminea for fresh (45.58 mg/kg) and smoked (16.32 mg/kg) are far higher than Malaysia Food Regulation, 1985 (10 mg/kg) and Food Standard Australia and New Zealand standards, 1991 (10 mg/kg). On the other hand, the concentration of Cu in fresh C. fluminea (13.75 mg/kg) and smoked C. fluminea (12.60 mg/kg) are higher than the European Union Commission Standard, 2016 (10 mg/kg) and lower than the Malaysia Food Regulation, 1985 (30 mg/kg). Based on the results obtained, it shows that smoked C. fluminea collected from hawkers in the district of Tumpat are safe in terms of Cr and Zn but it is unsafe for the Mn and Cu parameters if consume more than 100 g/day/person.